A narrative review of factors influencing rider performance and horse welfare in equestrian activities - Balog, O.; Havanecz, K.; Csányi, T.; Ökrös, C.; Tóth, L.; Berki, T. (Frontiers in Sports and Active Living, 2025)
Equestrian sport is a unique multi-species discipline in which the performance of a horse-rider dyad depends on the harmonious interaction of two athletes with distinct biomechanics and needs. Although the sport contributes substantially to the global economy and is the only Olympic event involving two species, research on rider-centered factors has been fragmented. Current narrative review centered peer-reviewed evidence addressing three questions: (RQ1) how rider biomechanics and posture influence horse performance and welfare; (RQ2) what causes and consequences rider asymmetry has; and (RQ3) how riders` fitness, health and training practices affect performance and well-being. Electronic searches of five databases—namely PubMed, Web of Science, Scopus, SPORTDiscus and Google Scholar—covering 2000 to July 2024 retrieved 83 records; 17 studies met the inclusion criteria. Correct pelvic orientation, dynamic trunk control and symmetrical weight distribution were consistently associated with improved saddle pressure distribution and better equine gait. Asymmetries in riders` posture, whether inherent or acquired, contributed to uneven loading and degraded performance, yet many riders were unaware of their imbalances. Studies on fitness and training showed that equestrians often neglect structured off-horse conditioning despite moderate-to-vigorous cardiovascular demands during riding. Targeted core training programmes, cross-training and nutritional support improved balance and reduced back pain. Taken together, the literature points to a need for holistic interventions that combine biomechanical assessment, correction of asymmetry and structured fitness programmes to support both the rider and their horse.